THE EFFECT OF ADDING PROBIOTICS THROUGH DRINKING WATER TO THE BROILER APPEARANCE - I P. G. O., Sudartama; Astawa, I P. A.; Suasta, I M. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019DO - 10.24843/ejpt.2019.v07.i03.p06, 2019)
This research aims to know the effect of adding probiotick on the appearance of broiler chicken. This research was conducted in the cage of a farmer located in Candikusuma Village, Melaya Sub-District, Jembrana Regency, Bali Province for 5 weeks. The design used was a Completely Randomized Design (CRD) with 4 treatments P0, P1, P2, P3 and 4 replication, each replicator consists of 20 broiler chicken tails, total broiler chicken used by 320 tails. The treatment given is, P0: without provision of probiotics, P1: the addition of 0,5 ml of probiotics given through drinking water, P2: : the addition of 1 ml of probiotics given through drinking water, and P3: the addition of 1,5 ml of probiotics given through drinking water. Drinking water is given ad libitum and all treatments are given commercial feed with the same number and content of nutrition. The obseved variables include consumption of ration, final body weight, weight boens, feed conversion rasio, drinking water consumption. The data obtained wiil be analyzed by analysis of variace, if there are significant differences (P<0,05), then followed by a multiple distance test from Duncan. The results showed that the consumption of feed ration in 1 ml treatment were significantly different (P<0,05), while on variables in the final body weight, body weight gain and drinking water consumption in the treatment of  P1, P2, dan P3 were not significantly different (P>0,05). Based on the results of this study concluded that the giving of probiotics through drinking water at a dose of 0,5 ml, 1ml, dan 1,5 ml id not affect significantly on final body weight, body weight gain, feed conversion rasio (FCR), and drinking water consumption broiler chicken. But can significantly influence on consumption of ration.     Keywords : appearance, broiler, probiotics